A Review of Autonomous Decision-making by UAVs - Wang, Zhongchi (International Journal of Mechanical and Electrical Engineering, 2024)
Drone autonomous decision-making technology is a key component of the UAV system, which aims to enable UAVs to autonomously complete tasks in complex and dynamic environments, reducing human intervention. This paper reviews the current status and development of autonomous decision-making technology of UAVs, mainly covering key technologies such as perception and environmental modeling, path planning and navigation, decision-making and control, and multi-UAV systems. This paper also explores the application scenarios of autonomous decision-making technology for drones in military and civilian fields, such as reconnaissance and surveillance, logistics and distribution, agricultural monitoring, and disaster relief. In view of the challenges faced by the current technology, such as computing resources, environmental complexity, security and privacy protection, this paper proposes possible solutions and research directions.